Vitamin D and Calcium Pharmaceutical Supplements: All we Need to Know to Choose the Right One - Majid, Hafsa; Zehra, Nawazish; Khan, Ablooj; Jafri, Lena; Khan, Aysha Habib (Pakistan Armed Forces Medical Journal, 2024)
Calcium and Vitamin D deficiency is highly prevalent in Pakistan. Both micronutrients have a significant role in human growth and development. Supplementation becomes essential when the available natural sources like food and sunlight, cannot replenish the deficiencies. Nevertheless, it is critical that while prescribing Calcium or Vitamin D supplements, physicians should know the composition and specific application of each supplement. This review explores the different types of Calcium and Vitamin D pharmaceutical supplements available in the market their composition, indication and contraindications. Data of Calcium and Vitamin D supplements has been collected by Pakistani drug sites databases, including ‘Drug Infosys (www.druginfosys.com)’, ‘Dawaee.pk’, ‘Sehat.com.pk’ and ‘Medicine Net’ by pharmacists and orthopaedists. The commonly prescribed supplements are Cholecalciferol (Vitamin D) and Calcium Carbonate (Calcium). Over time, an increase in market share of Vitamin D and Calcium supplementations is due to their over-the-counter availability, increased physicians’ prescriptions, and self-prescribed use by the population. There is a need to develop national guidelines and policies to safeguard the population’s health at large.